Spontaneous Osteoarthritis in Dogs - Clinical Effects of Single and Multiple Intra-articular Injections of Hyaluronic Acid - Lee, Eunbee; Lee, Mun-Ik; Kim, Sehoon; Kang, Byung-Jae (Acta Scientiae Veterinariae, 2023)
Background: The treatments of osteoarthritis (OA) are commonly conservative and multimodal to relieve pain and improve movement. Intra-articular injection of hyaluronic acid (IAHA) has been studied as a treatment option for OA in dogs. IAHA helps restore the viscoelasticity of the synovial fluid and relieves the clinical symptoms of OA. However, the efficacy of IAHA in dogs is still a controversial subject. This study aims to confirm the IAHA effect in dogs with spontaneous OA and to compare the effectiveness depending on the number of injections. Materials, Methods & Results: Thirty dogs with spontaneous OA were assigned to a single injection group (n=17) and a 3-weekly injections group (n=13). Dogs weighing less than 10 kg were injected 1 mL of HA to the OA joint, and more than 10 kg dogs were injected 2 mL of HA. In the case of the 3-weekly injections group, the same amount was administered 3 times at 1-week intervals. After the injection, physical and orthopedic examinations were performed to check for complications. Radiographic OA score was evaluated before and 3 months after the injection to confirm and to evaluate the progression of OA. Clinical symptom evaluations were performed on pre-injection, 1-, 2-, and 3-months post-injection. They consisted of the clinical lameness score by veterinarians and Canine Brief Pain Inventory (CBPI) by owners. Results were compared with unpaired t-test, repeated-measures ANOVA with Tukey’s or Sidak’s multiple comparison test, or Wilcoxon test, with P < 0.05. Patients had a median age of 9 years (range 3 to 16 years) and a bodyweight of 4.8 kg (range 2 to 48 kg). No systemic side effects or major complications were detected during the trial period. IAHA produced temporary pain and discomfort in 6 cases. There was no change in the radiographic OA score before and 3 months after injections in both groups, and the difference between groups was not confirmed. In both groups, the clinical lameness score significantly decreased at 1, 2, 3 months after injection compared with pre-injection. The score was lower at 3 months after the injection than at 1 month. The clinical lameness score had no significant difference between the groups. Similarly, CBPI was all decreased in the single injection group and 3-weekly injections group compared to pre-injection, and the score at 3 months post-injection was lower than at 1 month. No significant differences between the groups were found in CBPI. Discussion: Most studies on the efficacy of IAHA in canine OA have been conducted using an experimental model, so studies on spontaneous canine OA are insufficient. This study confirmed that IAHA improves clinical symptoms such as pain relief and movement improvement in spontaneous OA dogs using CBPI and clinical lameness score. In order to confirm the optimal IAHA protocol, a single IAHA and 3-weekly IAHA were compared. The result shows that clinical symptoms improved in both single and 3-weekly injections groups, but no significant difference was confirmed during the 3-month study period. These findings may suggest that a single IAHA may have a similar effect to multiple IAHA, and repeated injections are unnecessary. In humans and canine OA models, it is reported that the effect of IAHA was maintained for 6 months. This study showed that the effect of IAHA was maintained for 3 months study period and that clinical symptoms improved at 3 months than at 1 month. In conclusion, these findings suggested that IAHA improves clinical symptoms in dogs with spontaneous OA, and a single IAHA showed a similar effect to 3 weekly IAHA. Keywords: canine, treatment, hyaluronic acid, intra-articular injection, osteoarthritis.